Severe emphysematous cystitis: Outcome after seven days of antibiotics - Sereno, Maria (McGill University, 2011)
We present the case of a 70-year-old woman with emphysematous cystitis. She was a diabetic patient and she was on chemotherapy treatment for a breast cancer. She complaint of severe asthenia and pain in her right lower extremity, but no fever or urinary symptoms. A computed tomography (CT) scan was suggestive of severe emphysematous cystitis. Emphysematous cystitis is a rare clinically entity, more commonly seen in diabetic, immunocompromised patients. A conservative treatment approach using antibiotics and bladder catheterization is typically successful, with a complication rate less than 20%.